Creative Interventions for Teaching Empathy in the Counseling Classroom. Issue 1 (2nd January 2018) - Bell, Hope
ABSTRACT: Empathy is a foundational, necessary component of successful counseling. Relaying an understanding of empathy, including the components and science behind the phenomenon, is critical to the development of counselors-in-training. In addition, creative practice is a pillar of professional counseling, and is linked to experiential learning and meaningful integration of new knowledge in counselor education. The purpose of this article is to provide a review of the definitions of empathy, provide current literature on the science of empathy, and discuss specific creative interventions to use within counseling courses to increase empathic knowledge and skills.